2017
DOI: 10.1021/acs.jafc.7b00912
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Spring Barley and Common Radish on the Introduction of Ionic Liquids Containing Asymmetric Cations to the Soil

Abstract: The harmful effect of ionic liquids (ILs) on the environment is one of the important elements of scientific research conducted around the world. This study presents the effect of ionic liquids, containing the asymmetric cations benzyltrimethylammonium chloride [BenzTMA][Cl] and benzyltriethylammonium chloride [BenzTEA][Cl], on physiological and biochemical changes in common radish plants and spring barley seedlings. The examined ILs demonstrated low toxicity to higher plants. The compound that exhibited higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Although ILs are safe to the atmosphere due to their low vapor pressure, their environmental accumulations, excellent miscibility with most media, and high stability have made them a persistent threat to environmental waters and soils. Actually, a large number of studies have shown that ILs can cause toxicity to various organisms, such as algae, bacteria, fish, plants, and even mammalian cell lines . Therefore, the toxicity risk of ILs and the underlying mechanisms must be elucidated to ensure their large-scale safe applications.…”
Section: Environmental Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Although ILs are safe to the atmosphere due to their low vapor pressure, their environmental accumulations, excellent miscibility with most media, and high stability have made them a persistent threat to environmental waters and soils. Actually, a large number of studies have shown that ILs can cause toxicity to various organisms, such as algae, bacteria, fish, plants, and even mammalian cell lines . Therefore, the toxicity risk of ILs and the underlying mechanisms must be elucidated to ensure their large-scale safe applications.…”
Section: Environmental Significancementioning
confidence: 99%
“…The toxicity of ILs has been evaluated by resorting to different biological models, including bacteria and fungi, invertebrates, fish, algae, plants, and mammalian cell lines . Recently, a high level of an IL (i.e., 1-octyl-3-methylimidazolium, also referred to as M8OI) was detected in soils around to a landfill waste site in the northeast of England, and the IL was found to have the potential to trigger primary biliary cholangitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following their extensive use, some ILs will inevitably enter the local environment [13,14]. Because of their high stability, they may be a source of persistent pollution in the environment [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many beneficial properties of ionic liquids (ILs, composed entirely of ions with melting points less than 100 °C) have been identified and exploited. , Their physicochemical properties such as melting point, density, viscosity, volatility, and solubility properties can be optimized by selecting the appropriate counter ions. , One of the most promising advantages of ILs is their very low vapor pressures, which result in low volatility . From the first generation (with designable physical properties) through the second generation (with oriented chemical properties), IL development has proceeded to a third generation (with targeted biological properties) .…”
Section: Introductionmentioning
confidence: 99%